Evaluation of cardiovascular risk-lowering health benefits accruing from laboratory-based, community-based and exercise-referral exercise programmes. Issue 1 (1st March 2016) - Webb, R; Thompson, J E S; Ruffino, J-S; Davies, N A; Watkeys, L; Hooper, S; Jones, P M; Walters, G; Clayton, D; Thomas, A W; Morris, K; Llewellyn, D H; et al.
Abstract : Background: To evaluate the ability of community-based exercise programmes to facilitate public participation in exercise and hence improved cardiovascular health, we assessed the respective impacts of: a continuously monitored exercise programme based within our university (study 1); a Valleys Regional Park-facilitated community-based outdoor exercise programme (study 2); a Wales National Exercise Referral Scheme-delivered exercise-referral programme (study 3). Methods: Biomolecular (monocytic PPARγ target gene expression), vascular haemodynamic (central/peripheral blood pressure, arterial stiffness), clinical (insulin sensitivity, blood lipids) and anthropometric (body mass index, waist circumference, heart rate) parameters were investigated using RT-PCR, applanation tonometry, chemical analysis and standard anthropometric techniques. Results: In studies 1–3, 22/28, 32/65 and 11/14 participants adhered to their respective exercise programmes, and underwent significant increases in physical activity levels. Importantly, beneficial effects similar to those seen in our previous studies (eg, modulations in expression of monocytic PPARγ target genes, decreases in blood pressure/arterial stiffness, improvements in blood lipids/insulin sensitivity) were observed (albeit to slightly differing extents) only in participants who adhered to their respective exercise programmes. While study 1 achieved more intense exercise and more pronounced beneficial effects, significant cardiovascular risk-lowering health benefits related to biomolecular markers, blood pressure, arterial stiffness and blood lipids were achieved via community/referral-based delivery modes in studies 2 and 3. Conclusions: Because cardiovascular health benefits were observed in all 3 studies, we conclude that the majority of benefits previously reported in laboratory-based studies can also be achieved in community-based/exercise-referral settings. These findings may be of use in guiding policymakers with regard to introduction and/or continued implementation of community/referral-based exercise programmes.